Extraction and Characterization of Chitin from Leucaena Leococephala - Harliza Abd Razak, Noor; Shahira Tajul Arus, Shareena; A . Zainuddin, N. (International Journal of Engineering and Technology, 2018)
In this research, a new source of chitin was proposed. Chitin was extracted leucaena leucocephala pods using NaOH and HCl solutions for deproteination and demineralisation, respectively. The purposes of this research were to characterize chitin by extraction of LL pods at different length and aging with 6M HCL and 12M of NaOH by using TGA and elemental Analysis. Thermal property characterization of chitin from leucaena leucocephala pods (LL) extraction was obtained by using thermogravimetric analysis (TGA) and elemental analysis. The TGA and Elemental Analysis then tested the prepared samples for the thermal property. For TGA, the results show development stage at LL (Set 6) has the highest thermal stability. However, for elemental analysis, the results show that the degree of deacetylation is the highest for carbon-nitrogen ratio at young LL because of high protein content. Furthermore, it was found that the DA decreased with an increasing thermal property.Â Â